Energy efficient, clean and solvent free photochemical benzylic bromination using NBS in concentrated solar radiation (CSR) - Deshpande, S.; Gadilohar, B.; Shinde, Yogesh; Pinjari, D.; Pandit, A.; Shankarling, G. (2015)
© 2015 Elsevier Ltd. An environmentally benign, clean, solvent free approach for the benzylic bromination have been developed using concentrated solar radiation (CSR). CSR methodology was used as an energy source to the reaction media. The protocol was found to be superior to the conventional photochemical and thermal methods in terms of reaction time and total energy requirement. This method was adapted with concentrated solar radiations in solvent free conditions without the use of radical initiators and has proved to provide good yields. Incorporation of renewable energy source, minimisation of raw materials makes the process not only green but energy efficient also.